2003
DOI: 10.1089/089771503770195786
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and Glial Cell Number in the Hippocampus after Experimental Traumatic Brain Injury: Analysis by Stereological Estimation

Abstract: Fluid percussion (FP) brain injury causes spatial memory dysfunction in rats regardless of injury location (midline vs. lateral). Standard histological analysis of the injured brains shows hippocampal neuronal loss after lateral, but not midline FP injury. We have used the optical volume fractionator (OVF) stereological procedure to quantify neuronal loss and glial proliferation within specific subregions of the hippocampus after midline or lateral FP injury. The OVF method is a design-based cell counting proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
146
3
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 70 publications
13
146
3
1
Order By: Relevance
“…Accordingly, there are consistent, quantifiable focal and diffuse histopathologies that are all potential therapeutic targets (Dietrich et al, 1994, Bramlett et al, 1997, Ciallella et al, 2002, Grady et al, 2003, Suzuki et al, 2003, Suzuki et al, 2004, Witgen et al, 2005. In our studies, we found that rolipram, a selective PDE IV antagonist, improved histopathology at multiple levels.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Accordingly, there are consistent, quantifiable focal and diffuse histopathologies that are all potential therapeutic targets (Dietrich et al, 1994, Bramlett et al, 1997, Ciallella et al, 2002, Grady et al, 2003, Suzuki et al, 2003, Suzuki et al, 2004, Witgen et al, 2005. In our studies, we found that rolipram, a selective PDE IV antagonist, improved histopathology at multiple levels.…”
Section: Discussionsupporting
confidence: 63%
“…The parasagittal FPI model results in stereotypical neuronal death in the parietal cortex overlying the cortical contusion and in the CA3 region of the hippocampus (Grady et al, 2003, Witgen et al, 2005. Treatment of rolipram during TBI and for 3 days following moderate FPI improved neuronal survival in both the parietal cortex (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Knockdown of the NMDA-type glutamate receptor 1 in a mere 6% to 7% of CA1 neurons in the hippocampus is enough to significantly impair memory formation (Cheli et al, 2006). The FPI model, without any accompanying hypoxia, does not result in substantial neuronal loss throughout the hippocampus with the exception of the CA3 and hilar subregions, but does result in significant hippocampal-dependent memory impairments (Lyeth et al, 1990;Carbonell et al, 1998;Grady et al, 2003). Accordingly, hippocampal LTP is impaired and subtle structural damage is seen in the hippocampus after TBI (Sanders et al, 2000;Golarai et al, 2001;Scheff et al, 2005).…”
Section: Figurementioning
confidence: 99%
“…Rodent models of TBI, including the lateral fluid percussion (FP) brain injury model also produce persistent impairments in learning and memory [61], which have been attributed to neuronal injury and dysfunction in the hippocampus [11,27,33,47]. Within the hippocampus, there is a significant loss of neurons in the CA3 pyramidal cell layer and the hilus of the dentate gyrus on theipsilesional side following a FP injury [23]. In addition, in the hilus there is evidence of bilateral injury, which includes damage to neuronal cytoskeletal proteins [34], activation of injury related signal transduction pathways [62], and abnormal electrophysiology [47].…”
Section: Introductionmentioning
confidence: 99%